Werner Sombart: a stranger in sociological tradition? - Graça, João Carlos (Sociedade e Estado, 2022)
Endowed with a great fame in the main sociological milieus worldwide roughly a century ago, the name of Werner Sombart tended afterwards to fall into a penumbra of near-oblivion, being normally excluded from the current sociological pantheon. This was much probably due to, among other factors, his late support for Nazism. Nevertheless, his considerations on the relationship of capitalism with war, luxury and religious ethics, particularly the Jewish ethics, the value ambivalence of capitalist mentality (with the bourgeois-entrepreneur antinomy), the periodization and future trajectory of capitalism, the singularities of North-American political life, were all once very renowned, and are still more than worthy of careful reflection. Sombart left several unresolved questions, which are still capable of addressing us directly and vividly today. Being a half-forgotten author of the sociological tradition, he is nevertheless, under more than one perspective, plentifully our contemporary.